الكشف عن سمية عزلات فطرية من بذور وكسبة فول الصويا باستخدام بعض الاختبارات الحيوية - المغربي, صباح; حسن, محمود; عليو, نهى (Latakia University Journal -Biological Sciences Series, 2019)
تم اختبار/103/ عزلة فطرية نقية من 23 عينة من بذور وكسبة فول الصويا تتبع إلى 17 جنساً فطرياً منها Fusarium, Rhizopus, Absidia, Mucor, Alternaria Pythium,، حيث درست سمية هذه العزلات على: إنبات بذور الرشادLepidium sativum، نمو سلالة من البكترياBacillus subtilis FZB27، وفطر الخميرة Saccharomyces cerevisiae، وذلك على مستنبتي PDA وTSA إضافةً لمستنبتPSA الخاص بعزلات الجنس Fusarium. استخلصت المزارع الفطرية بالأسيتون 80% ونفذت الاختبارات في أطباق إليزا، حيث تبين وجود39 عزلة متوسطة السمية في الاختبارات الثلاثة، 8 عزلات شديدة السمية أعاقت إنبات بذور الرشاد، و17عزلة منعت نمو البكتريا، وبدت سمية العزلات عالية على مستنبت TSA في اختبار Ls مقارنةً بالمستنبتات الأخرى، وكانت معظم عزلات الجنس Fusarium شديدة السمية على مستنبتي PDA،PSA بالنسبة لاختبارBs، ولم تظهر فروق في السمية على المستنبتات بالنسبة لاختبارSc. A total of /103/ pure fungal isolates from 23 samples of soybean seeds and meal belonging to /17/ genera Alternaria, Mucor, Absidia, Rhizopus, Fusarium, Pythium were tested. The toxicity of isolates was studied on: germination of garden cress Lepidium sativum seeds, growth of bacterial strain Bacillus subtilis FZB27, and yeast fungi Saccharomyces cerevisiae on PDA, TSA medias and PSA for Fusarium isolates. The fungal cultures were extracted by Acetone 80%, and tests were performed in Elisa plats. We found 39 isolates with medium toxicity on three testes, 8 isolates with high toxicity inhibit seeds germination, and 17 isolates prevent the bacteria growth. The toxicity was high on TSA media in Ls test compared with other Medias. Most of Fusarium isolates were of high toxicity on PDA, PSA Medias in Bs test. No differences in toxicity appeared on Medias in Sc test.